Enhanced Instructed Fear Learning in Delusion-Proneness - Louzolo, Anaïs; Almeida, Rita; Guitart-Masip, Marc; Björnsdotter, Malin; Lebedev, Alexander; Ingvar, Martin; Olsson, Andreas; Petrovic, Predrag (Frontiers in Psychology, 2022)
Psychosis is characterized by distorted perceptions and deficient bottom-up learning, including associative reward learning and fear conditioning. This has been interpreted as reflecting unstable priors in low-level predictive coding systems. Paradoxically, overly strong beliefs and delusions are also present in psychosis-associated states. In line with this, research has suggested that patients with psychosis and associated phenotypes rely more on high-order priors, when such are present, to interpret perceptual input. In this behavioural and fMRI study, we asked whether fear learning is stronger in psychosis-related phenotypes when it is mediated on an explicit level - in contrast to low-level fear learning, such as fear conditioning, that has repeatedly been shown to be weaker in these groups of individuals. More specifically, we used an instructed fear learning paradigm to study the impact of verbal information on evaluative fear learning in relation to delusion proneness - a trait associated with psychotic disorders that is present in healthy individuals. In line with our hypothesis, we observed significantly larger instructed fear learning, associated with activation of lateral orbitofrontal cortex, in delusion-prone individuals (n=20) compared to non-delusion-prone subjects (n=23; n=20 in fMRI study). Moreover, delusion-prone subjects also showed a stronger functional connectivity between right lateral orbitofrontal cortex and regions processing fear and pain, in the effect of instructions on fear processing and in the main effect of instructions, respectively. Our results suggest that strong high-level fear learning co-exists with previously reported weak low-level fear learning, in psychosis-associated states.